Spatiotemporal expression patterns of natriuretic peptides in rat testis and epididymis during postnatal development - Özbek, Mehmet; Hitit, Mustafa; Öztop, Mustafa; Beyaz, Feyzullah; Ergün, Emel; Ergün, Levent (Wiley, 2019)
Natriuretic peptide (NP) family is composed of atrial, brain and C-type NP (NPPA, NPPB and NPPC). Here, we aimed to investigate NP expression in testis and epididymis during postnatal development. NPPA expression was observed in gonocytes at prepubertal period but in only spermatocytes in pachytene and leptotene/zygotene stage at pubertal period. In prepubertal and pubertal periods, we detected NPPB expression in only Leydig cells. However, NPPC expression was detected in all of the gonocytes and Sertoli cells, spermatocytes and some interstitial cells in prepubertal and pubertal periods. In postpubertal and mature periods, NPPA and NPPB staining were detected in Leydig cells, elongated and round spermatids but not in spermatogonia and spermatocytes. However, we observed NPPC expression in all cells of the seminiferous tubules and Leydig cells in the postpubertal and mature periods. Epididymal epithelium showed intense NPPC expression during postnatal period but weak NPPA and NPPB expression in prepubertal and pubertal periods. The expression of three NPs in the testis significantly increased after puberty. In conclusion, puberty had a significant effect on NP expression in testis. Unlike NPPA and NPPB, expression of NPPC in all cells of the seminiferous tubule suggests that NPPC is effective in each step of spermatogenesis.
Keywords: Epididymis; Male; Natriuretic Peptide, C-Type; Rats; Spatio-Temporal Analysis; Natriuretic Peptide, Brain; Testis; Animals; Sexual Maturation; Spermatogenesis; Atrial Natriuretic Factor